Treatment Non-Compliance in Patients with Schizophrenia - Subedi, Sandip; Paudel, Kamala; Thapa, Dev Kumar (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Non-compliance to medication in Schizophrenia is a common problem. It leads to frequent recurrence of Psychosis which has negative impact on individuals and their families. Understanding and reducing non-adherence is therefore a key challenge to quality care for patients with Schizophrenia. This study was conducted with the aim of determining the incidence and factors associated with medication non-compliance among patients suffering from schizophrenia. MATERIAL AND METHODS: This cross-sectional study included 94 schizophrenic subjects who visited psychiatric OPD of tertiary level hospital. Disproportionate stratified random sampling method was applied to collect the data. Socio-demographic data sheet, data sheet to collect the various factors of compliance and the 8-item Morisky Medication Adherence Scale (MMAS-8) were used for data collection by interview method. RESULTS: The prevalence of non-compliance was 89.4%. With regards to association between noncompliance and demographic characteristics, there was high non-compliance rate in age below 40 years (54.2%), male (52.1%), married (64.8%) and low economic status (52%). Medication non-compliance were high in patients with medication side effects dizziness (60.6%), sedation (66%), longer duration of illness (92.8%) & having 1-3 pills (47.8%). CONCLUSION: Medication Non-Compliance in Schizophrenia was high. Measures that can increase compliance like psycho-educational programmes on compliance and the active involvement of the relatives and significant others in the management of patients of mentally ill patients are recommended.